Osseous metaplasia in hyperplastic gastric polyp - A rare case report with review of literature - Pomilla Singh; Ankush Nayyar; Manjiri N. Karandikar (Elsevier, 2020)
Osseous metaplasia (OM), or heterotopic ossification, refers to the formation of bone at extra-skeletal sites. It has been documented in various solid tumors including gastrointestinal (GI) tumors but the occurrence of this phenomenon in benign gastric polyps is very rare. The literature lacks information on its etiology as well as clinical outcomes and prognosis.